2019
DOI: 10.1051/e3sconf/201913201020
|View full text |Cite
|
Sign up to set email alerts
|

Automation of management processes

Abstract: Artificial intelligence and service automation are the key to these kinds of new, product-related services. They increasingly penetrate the traditional mechanical and plant engineering sector and open up potentials for innovative services. Tourism services providers are going through rapid changes and the role of Information and Communication Technology, artificial intelligence and service automation is increasing in all spheres of the service management system. When the organization is threatened by environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…This practice can positively receive support from all of the stakeholders that were encouraging on integration, and better communications throughout the supply chain network. From a previous study, it was pointed out that traditional procurement process within the design and build contract arrangement proven to increase the difficulty for engagement of environmentally friendly material, because of extreme concern from the contractors for the completion dateline and the additional costs incurred [6]. Some researchers identified that using lean techniques is the best procurement practice in construction industry that tremendously increase productivity [7].…”
Section: E-procuremntmentioning
confidence: 99%
“…This practice can positively receive support from all of the stakeholders that were encouraging on integration, and better communications throughout the supply chain network. From a previous study, it was pointed out that traditional procurement process within the design and build contract arrangement proven to increase the difficulty for engagement of environmentally friendly material, because of extreme concern from the contractors for the completion dateline and the additional costs incurred [6]. Some researchers identified that using lean techniques is the best procurement practice in construction industry that tremendously increase productivity [7].…”
Section: E-procuremntmentioning
confidence: 99%